Effectiveness of an angiotensin II receptor blocker losartan as monoand combined therapy in hypertensive patients with various levels of renin-angiotensin-aldosterone system activity - Sh. V. Akhadov; G. R. Ruzbanova; G. S. Molchanova; S. N. Khoreva (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To study the role of angiotensin II receptor blockers (ARB), in particular, losartan, in mono- and combined therapy of patients with arterial hypertension (AH) and various renin-angiotensin profiles. To identify the patients with maximal effectiveness of antihypertensive treatment and maximal improvement in the levels of reninangiotensin-aldosterone system (RAAS) parameters. Material and methods. The study included 399 patients, aged 18-65 years (mean age 53,4±7,6 years), with essential AH and mean levels of systolic and diastolic blood pressure (SDP, DBP) of 194,8±8,8 and 114,8±4,8 mm Hg, respectively. Plasma renin activity (PRA) and plasma aldosterone concentration (PAC) were measured by radioimmune methods. Results. Losartan (50 mg/d) reduced DBP in patients with PRA 0,22-1,0 ng/ml/h and PAC/PRA 5-23 by 9,5% (р<0,05-0,01); in patients with PRA 1,0-3,0 ng/ml/h and normoaldosteronism – by 7,4% (p<0,05-0,01); in all the other subgroups – by 22,1-32% (p<0,01).Conclusion. During ARB treatment, PAC reduction positively correlated with baseline PAC levels and negatively correlated with the magnitude of reactive PRA elevation. In patients with PRA <0,22 ng/ml/h, anti-aldosterone effect of ARB was attenuated. Losartan monotherapy (50 mg/d) normalised BP in all AH patients, with an exception of individuals with normoaldosteronism. The combination of losartan with nifedipine retard demonstrated wide therapeutic spectrum and good antihypertensive effect. The combination of losartan and atenolol was effective in all patients with increased sympatho-adrenal system activity